Blended learning with digital story telling model of students in English courses of Chinese primary education: Need assessment analysis - Peng, Lifei; Petsangsri, Sirirat; Cui, Jianming (Edelweiss Applied Science and Technology, 2025)
The current study aimed 1) to assess the needs of students in English courses at primary schools in China, focusing on blended learning, digital storytelling, English communication skills, and self-efficacy; 2) to develop blended learning with a digital storytelling model. The researcher employed a stratified random sampling method to select four key public primary schools from ten key public primary schools in Tongren City, China. Furthermore, English teachers from those four selected primary schools were invited to assist in the process of distributing the questionnaires, with 100 students sampled from each school, totaling 400 participants. Descriptive statistical methods were used to analyze the collected data, examining the mean scores across 12 items. Results indicated that the mean values ranged from 3.81 to 4.63. Among these, seven items had mean scores exceeding 4.21, reflecting a high need for elements such as additional online English learning materials, English movies and videos, enhanced speaking skills, and greater confidence in learning English. The remaining five items had mean scores above 3.41, indicating a moderate level of need. Moreover, the blended learning with the digital storytelling model was composed of ten steps, including online and offline activities.